2023
DOI: 10.1371/journal.pone.0268428
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of pulmonary physiotherapy in hospitalized patients with severe COVID-19 pneumonia (PPTCOVID study): A prospective, randomised, single-blind, controlled trial

Abstract: Background Pulmonary physiotherapy (PPT) is an important treatment in the management of patients with different types of pulmonary disorders. We aimed to evaluate safety and efficacy of PPT in hospitalized patients with severe COVID-19 pneumonia. Methods In this randomised, single-blind, controlled trial, we enrolled hospitalized, non-intubated patients (18 to 75 years with oxygen saturation (Spo2) in free-air breathing ≤90%) with COVID-19 pneumonia at a referral hospital. Participants were randomly assigned… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 34 publications
0
8
0
2
Order By: Relevance
“…32,44,62,63,71,77,79,82,83,89,90,106,118,119,126,127 It is noteworthy that the studies with significantly improved mental component scores 71,89,90 often involved three or more types of training interventions, in contrast to studies that showed no improvement in mental component scores. 43,49,87,113,126,137 Additionally, the intervention delivery mode and supervision method appeared to exert minimal influence on QOL.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…32,44,62,63,71,77,79,82,83,89,90,106,118,119,126,127 It is noteworthy that the studies with significantly improved mental component scores 71,89,90 often involved three or more types of training interventions, in contrast to studies that showed no improvement in mental component scores. 43,49,87,113,126,137 Additionally, the intervention delivery mode and supervision method appeared to exert minimal influence on QOL.…”
Section: Resultsmentioning
confidence: 97%
“…Exercise capacity outcomes, including the Six-Minute Walk Test (6MWD) and the Sit-To-Stand Test (STS), were synthesized from data obtained in 16 RCTs. Out of these, 12 RCTs 31,[43][44][45][46][47]49,54,56,60,61,63,64 assessed 6MWD, revealing moderate-level evidence of improved walking outcomes in patients who underwent rehabilitation interventions compared to those receiving standard care (MD 38.18 [25.33, 51.03], I² = 88%) (Figure 4). Subgroup analysis by delivery mode indicated that tele-rehabilitation (MD 66.89 [32.15, 101.62], I² = 90%) appeared more effective than in-person rehabilitation 93.21], I² = 92%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since they are the most informa-tive about disorders of the function of external breathing [31,32,33], especially obstructive disorders [32,34,35], in Long COVID, their results are often ambiguous and require careful interpretation because of the understanding of the physiology of the new disease [12]. Thus, obstructive or restrictive changes were found in 17% of people, mainly after severe pneumonia, which later transformed into pulmonary fibrosis [36,37].…”
Section: огляди літератури / Literature Reviewsmentioning
confidence: 99%
“…An alternative technique for judging the mechanisms of shortness of breath in Long COVID is the assessment of saturation in physical exercise tests: the 3 -or 6-minute walk test (3/6MWT) or the 1-minute sit-to-stand test (1MSTST) [36,[38][39][40]. Desaturation (decrease in SpO 2 to 80%) during exercise has a direct correlation with spirometry and X-ray examination data [37], pO 2 and pCO 2 values in venous blood [40], the severity of clinical symptoms and DLCO level, which may be a consequence parenchymal and/or pulmonary vascular phenomena [41].…”
Section: огляди літератури / Literature Reviewsmentioning
confidence: 99%